HbA1c during early pregnancy reflects beta-cell dysfunction in women developing GDM. Issue 2 (1st November 2020) - Bozkurt, Latife; Göbl, Christian S; Leitner, Karoline; Pacini, Giovanni; Kautzky-Willer, Alexandra
Abstract : Introduction: It is of current interest to assess eligibility of hemoglobin A1c (HbA1c) as a screening tool for earlier identification of women with risk for more severe hyperglycemia in pregnancy but data regarding accuracy are controversial. We aimed to evaluate if HbA1c mirrors pathophysiological precursors of glucose intolerance in early pregnancy that characterize women who develop gestational diabetes mellitus (GDM). Research design and methods: 220 pregnant women underwent an HbA1c measurement as well as an oral glucose tolerance test (OGTT) with multiple measurements of glucose, insulin and C-peptide for evaluation of insulin sensitivity and beta-cell function at 16th gestational week (IQR: 14–18). Clinical follow-ups were performed until end of pregnancy. Results: Increased maternal HbA1c ≥5.7% (39 mmol/mol) corresponding to pre-diabetes outside of pregnancy was associated with altered glucose dynamics during the OGTT. Pregnancies with early HbA1c ≥5.7% showed higher fasting (90.4±13.2 vs 79.7±7.2 mg/dL, p<0.001), mean (145.6±31.4 vs 116.2±21.4 mg/dL, p<0.001) as well as maximum glucose concentrations and tended to a delay in reaching the maximum glucose level compared with those with normal-range HbA1c (186.5±42.6 vs 147.8±30.1 mg/dL, p<0.001). Women with increased HbA1c showed impaired beta-cell function and differences in disposition index independent of body mass index status. We observed a high specificity for the HbA1c cut-off of 5.7% for GDM manifestation (0.96, 95% CI 0.91 to 0.98) or need of glucose-lowering medication (0.95, 95% CI 0.90 to 0.98) although overall predictive accuracy was moderate to fair. Further, elevated HbA1c was associated with higher risk for delivering large-for-gestational-age infants, also after adjustment for GDM status (OR 4.4, 95% CI 1.2 to 15.0, p=0.018). Conclusions: HbA1c measured before recommended routine screening period reflects early pathophysiological derangements in beta-cell function and glucose disposal that are characteristic of GDM development and may be useful in early risk stratification.